A single point mutation on FLT3L-Fc protein increases the risk of immunogenicity - Qin, Dan; Phung, Qui; Wu, Patrick; Yin, Zhaojun; Tam, Sien; Tran, Peter; ElSohly, Adel M.; Gober, Joshua; Hu, Zicheng; Zhou, Zhenru; Cohen, Sivan; He, Dongping; et al. (Frontiers in Immunology, 2025)
IntroductionAs a crucial asset for human health and modern medicine, an increasing number of biotherapeutics are entering the clinic. However, due to their complexity, these drugs have a higher potential to be immunogenic, leading to the generation of anti-drug antibodies (ADAs). Clinically significant ADAs have an impact on pharmacokinetics (PK), pharmacodynamics (PD), effectiveness, and/or safety. Thus, it is crucial to understand, manage and minimize the immunogenicity potential during drug development, ideally starting from the molecule design stage.MethodsIn this study, we utilized various immunogenicity risk assessment methods, including in silico prediction, dendritic cell internalization, MHC-associated peptide proteomics, in vitro HLA peptide binding, and in vitro T cell proliferation, to assess the immunogenicity risk of FLT3L-Fc variants.ResultsWe identified a single point mutation in the human FLT3L-Fc protein that introduced highly immunogenic T cell epitopes, leading to the induction of T cell responses and thereby increasing the immunogenicity risk in clinical settings. Consequently, the variant with this point mutation was removed from further consideration as a clinical candidate.DiscussionThis finding underscores the necessity for careful evaluation of mutations during the engineering of protein therapeutics. The integration of multiple immunogenicity risk assessment tools offers critical insights for informed decision-making in candidate sequence design and therapeutic lead selection.